STUDI TERKAIT PROFITABILITAS DAN KUALITAS LAPORAN KEUANGAN - May Regina Angelica Situmorang; Hisar Pangaribuan (Jurnal Ekonomis, 2021)
This study aims to examine the effect of profitability and financial statements on banks listed on the Thailand Stock Exchange for the 2017-2019 period. Researchers are motivated by previous research on Indonesian banking which in this study provides results that show the practice of Income Smoothing in Indonesian banking. The researcher used statistical regression to analyze the data collected from the company's annual report. In Profitability the researcher uses the Return on Assets (ROA) and Return on Equity (ROE) variables to examine the quality of the financial statements, while the researcher uses the Total Accruals (TACit) variable which is reflected in the practice of Income Smoothing. The results of this study indicate that profitability has a significant effect on the quality of financial statements, which means that if the company's profit reporting is getting better, it is more likely that the company will practice Income Smoothing, and vice versa, so it can be concluded that the practice of Income Smoothing in Thai banking tends to be lower.